PENGUKUR TINGGI BADAN MENGGUNAKAN SENSOR ULTRASONIK BERBASIS MIKROKONTROLER ATMEGA328 DENGAN OUTPUT SUARA - Ignatius Agus Supriyono; Ferry Sudarto; Muhammad Khiabani Fakhri (CCIT Journal, 2016)
Measurement is important in the world of science. On these readings on the scale height measuring instrument manual that humans do have a level of accuracy and precision are less so frequent occurrence of human error. Then the required height gauges that can work automatically, perform the measurement process, read the measurement results, as well as notify the measurement results with the ATmega328 microcontroller-based voice output. Digital Height Measuring Circuit uses ultrasonic sensors are used to detect objects around sensor.Jika ultrasonic waves bounce back to the receiver, means there is an object in the vicinity of the sensor. The microcontroller will calculate the time it takes to receive ultrasonic waves and determine the distance between the sensor with the floor. Digital height gauge be important in minimizing human error that often occurs at the time of measurement manually. So as to improve efficiency in measuring height